Reservoir Forming Conditions and Enrichment Law of Tight Sandstone Gas in Upper Paleozoic in Ordos Basin - Jihua Zhang; Chi Zhang (Adsorption Science & Technology, 2022)
With the popularization of natural gas and the requirement of environmental protection, the development and utilization of natural gas are particularly important. The status of natural gas in China’s oil and gas exploration and development is constantly improving, and the country pays more and more attention to the exploitation and utilization of natural gas. The tight sandstone of Upper Paleozoic in Ordos Basin has the characteristics of low porosity, low permeability, and large area of concealed gas reservoirs. With the increasing demand for natural gas in China, systematic analysis and research on the geological conditions and enrichment law of large area gas reservoirs of tight sandstone of Upper Paleozoic in Ordos Basin to guide exploration and production also pose a great challenge to the current level of natural gas exploration and development in China. In order to solve this problem, this paper takes the Upper Paleozoic tight sandstone in Hangjinqi area in the north of Ordos Basin as the research object, summarizes the natural gas accumulation conditions of tight sandstone according to the geological characteristics of Ordos Basin, determines the main control factors of gas accumulation by superposition method in combination with the distribution characteristics of natural gas, simulates the dynamic process of gas accumulation, establishes the gas accumulation model, analyzes the conditions of gas accumulation and enrichment by statistical methods, summarizes the accumulation and enrichment rules of natural gas, and predicts the favorable exploration areas for natural gas. The results show that the relationship between hydrocarbon source rocks, traps, migration and transportation, and other reservoir-forming conditions and the distribution characteristics of natural gas is summarized, and the main controlling factors of reservoir-forming are determined by superposition method. We simulate the evolution process of faults, strata, oil, gas, and water flows in the study area and establish the dynamic reservoir-forming process of natural gas. By combining the reserve data with the reservoir source distance, reservoir facies type, and gas filling times, the reservoir-forming and enrichment conditions are studied by statistical analysis method, and the reservoir-forming and enrichment rules are summarized by combining the main controlling factors. The enrichment of natural gas is controlled by the development degree of source rocks, favorable tight sandstone combination, confluence channel, and local structure. According to the law of accumulation and enrichment, the division standards of favorable areas in different horizons are established, and the favorable exploration areas in the study area are predicted. The results provide theoretical data support for natural gas exploration in the study area.